FANTASI DAN PSIKOANALISIS DALAM DRACULA KARYA BRAM STOKER - Rida Wahyuningrum (OKARA: Jurnal Bahasa dan Sastra, 2011)
Based on Bram Stoker’s novel entitled Dracula translated by Mrs. Suwarni A.S., this paper tries to reveal fantasy and psychoanalysis through the elements of the novel such as theme, characters, and setting. The major characters of the novel are Van Helsing, Jonathan Harker, Mina Harker, Dr. Seward, Lucy Westenra, Quency Morris, and Arthur Holmwood. This paper is focusing on the elements of fantasy and anxiety, by observing the characters above. psychoanalysis centers on the unconsciousness along with anxiety and survival mechanism as the main discussion. This paper will hopefully be a kind of a shortcut to provide a small-scale coverage of such both psychoanalysis study and fantasy as well upon the novel characters.